(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article examines the impact of extralinguistic factors on the translation of phraseological units containing national and cultural components in Thomas Mayne Reid’s novel “The Headless Horseman”. The research focuses on historical, cultural, social and ethnographic aspects of nineteenth-century Texas and the American South that affect both the formation and translation of phraseological expressions. Particular attention is paid to the preservation of national-cultural coloring in the Russian translation of the novel. The study analyzes issues of equivalence, adequacy, and cultural transfer in the translation of phraseological units.